Multilayer negative electrode, secondary battery and electric equipment
By adopting a multi-layer negative electrode structure in lithium-ion batteries, the problem of capacity attenuation and degradation of kinetic performance of lithium-ion batteries when increasing silicon content or increasing negative electrode sheet thickness is solved, and the effect of both high capacity and excellent kinetic performance is achieved.
Patent Information
- Application Number
- CN202411974776.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
When existing lithium-ion batteries increase the negative electrode silicon content or increase the negative electrode sheet thickness, they face the problems of capacity attenuation acceleration and degradation of dynamic performance, and it is difficult to have high capacity and excellent dynamic performance.
A multi-layer negative electrode structure is adopted, including a negative electrode current collector and a multi-layer negative electrode active layer disposed on at least one side of the negative electrode current collector. The coatings meet the specific component usage and particle size structure relationships to improve the conductive network structure of the negative electrode sheet.
On the basis of larger thickness, the battery is given good dynamic performance, improves rate performance and cycle stability, and meets the needs of high energy density and fast charging applications.
Smart Images

Figure BDA0005220987430000081 
Figure BDA0005220987430000091 
Figure BDA0005220987430000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, in particular to a multi-layer negative electrode, a secondary battery and an electrical device. Background Art
[0002] With the widespread application of electrochemical energy storage in electric vehicles (EVs), the requirements and reliance on lithium-ion batteries (LIBs) have become higher, especially the demand for large-capacity batteries (such as 100kWh, range >700km). Silicon is considered to be an ideal negative electrode material for high-energy density batteries due to its high theoretical specific capacity and low lithium deintercalation potential. In order to further meet the demand for increasing battery capacity, it is necessary to increase the silicon content in the negative electrode or increase the thickness of the negative electrode sheet. However, 1) the increase in silicon content will lead to a larger volume expansion, which will accelerate the capacity decay; 2) Increasing the thickness of the negative electrode sheet will reduce the kinetic performance of the lithium battery and affect the application of fast charging.
[0003] Therefore, it is necessary to provide a multilayer negative electrode for a secondary battery having both high capacity and excellent kinetic performance. Summary of the invention
[0004] The object of the present application is to provide a multilayer negative electrode for a secondary battery having both high capacity and excellent kinetic performance.
[0005] To achieve the above-mentioned object, in a first aspect of the present application, a multilayer negative electrode is provided, the multilayer negative electrode comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, the negative electrode active layer comprising different coatings stacked, the coatings in the negative electrode active layer are sequentially recorded as the first layer, the second layer... to the mth layer from the side close to the current collector, the number of layers of the coating m≥3, any of the coatings independently comprises: carbon material, silicon material, conductive agent, binder, the multilayer negative electrode satisfies the following relationship:
[0006] 0.2≤f m =|K m / K m-1 -K m-1 / K m-2 | / S m-1 ≤1.2
[0007] K=C×H / B
[0008] S=(Dv90-Dv10) / Dv50
[0009] K m ≠K m-1 ≠K m-2
[0010] In the formula, C represents the mass percentage of the conductive agent based on the total weight of any of the coatings;
[0011] B represents the mass percentage of the silicon material based on the total weight of any of the coatings;
[0012] H μm represents the thickness of any of the coatings;
[0013] Dv10μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 10%;
[0014] Dv50μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 50%;
[0015] Dv90μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 90%;
[0016] The subscript m indicates the m-th layer of coating; the subscript m-1 indicates the m-1-th layer of coating; and the subscript m-2 indicates the m-2-th layer of coating.
[0017] As an embodiment of the present application, the thickness H of any of the coatings satisfies: 50 μm ≤ H ≤ 150 μm.
[0018] As an embodiment of the present application, the multilayer negative electrode satisfies: 0.1%≤C≤9%.
[0019] As an implementation manner of the present application, the multilayer negative electrode satisfies: 1%≤B≤15%.
[0020] As an embodiment of the present application, based on the total weight of any of the coatings, the mass percentage of the carbon material is recorded as A, and satisfies: 70%≤A≤99%.
[0021] As an implementation manner of the present application, based on the total weight of any of the coatings, the mass percentage of the binder is denoted as D, and satisfies: 0.1%≤D≤6%.
[0022] As an implementation of the present application, the particle size of the silicon material satisfies: 1 μm≤Dv10≤6 μm.
[0023] As an implementation of the present application, the particle size of the silicon material satisfies: 8 μm ≤ Dv50 ≤ 10 μm.
[0024] As an implementation of the present application, the particle size of the silicon material satisfies: 12 μm ≤ Dv90 ≤ 16 μm.
[0025] As an embodiment of the present application, the particle size of the carbon material satisfies: 1 μm≤Dv10′≤8 μm, where Dv10′ represents the particle size corresponding to when the cumulative volume of the carbon material reaches 10%, and the unit is μm.
[0026] As an embodiment of the present application, the particle size of the carbon material satisfies: 9 μm ≤ Dv50' ≤ 14 μm, D V 50' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 50%, and the unit is μm.
[0027] As an embodiment of the present application, the particle size of the carbon material satisfies: 16 μm ≤ Dv90' ≤ 24 μm, D V 90' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 90%, and the unit is μm.
[0028] A second aspect of the present application provides a secondary battery, which includes a positive electrode plate, an electrolyte, a separator, and the multilayer negative electrode described in the first aspect of the present invention.
[0029] A third aspect of the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the second aspect of the present application.
[0030] Compared with the prior art, the beneficial effects of this application are:
[0031] The present application uses multi-layer coating to rationally design parameters such as the amount of components in each coating layer so that adjacent coating layers satisfy the above-mentioned specific relationship, thereby improving the conductive network structure of the entire negative electrode plate, so that the negative electrode plate can still provide the battery with good dynamic performance on the basis of a larger thickness.
[0032] The thickness of the negative electrode plate of the present application can reach 200μm and above, up to 350μm, DCR≤0.42mΩ; 3C charging capacity retention rate ≥84.8%; 80% capacity retention rate cycle number at 25°C>1050 weeks. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0037] In a first aspect of the present application, a multilayer negative electrode is provided, the multilayer negative electrode comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, the negative electrode active layer comprising different coatings stacked, the coatings in the negative electrode active layer are sequentially recorded as the first layer, the second layer, ... to the mth layer from the side close to the current collector, the number of layers of the coating m≥3, any of the coatings independently comprises: a carbon material, a silicon material, a conductive agent, and a binder, and the multilayer negative electrode satisfies the following relationship:
[0038] 0.2≤f m =|K m / K m-1 -K m-1 / K m-2 | / S m-1 ≤1.2
[0039] K=C×H / B
[0040] S=(Dv90-Dv10) / Dv50
[0041] K m ≠K m-1 ≠K m-2
[0042] In the formula, C represents the mass percentage of the conductive agent based on the total weight of any of the coatings;
[0043] B represents the mass percentage of the silicon material based on the total weight of any of the coatings;
[0044] H μm represents the thickness of any of the coatings;
[0045] Dv10μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 10%;
[0046] Dv50μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 50%;
[0047] Dv90μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 90%;
[0048] The subscript m indicates the m-th layer of coating; the subscript m-1 indicates the m-1-th layer of coating; and the subscript m-2 indicates the m-2-th layer of coating.
[0049] The negative electrode of a secondary battery is usually composed of a negative electrode active material (silicon material, carbon material), a conductive agent, and a binder. The conductive agent provides an acceleration effect for the conduction of ions and electrons. Too low a content will affect the conductivity of the negative electrode, and too high a content will affect the capacity. The binder ensures good contact between the active materials and with the current collector, but too high a content will affect the kinetic properties of the negative electrode. A larger electrode sheet thickness can increase the amount of active material per unit area, thereby increasing the energy density of the battery, but increasing the thickness will deteriorate the kinetic properties of the negative electrode and increase the risk of lithium plating in the battery.
[0050] In addition, in the negative electrode, in addition to the influence of the amount of each component on the performance of the battery, the interaction between the components will also affect the distribution of each component in the active coating, thereby forming a coating with a different microstructure. The microstructure of the coating will affect the ionic conductivity and mechanical strength of the electrode, thereby affecting the rate performance and cycle stability of the battery.
[0051] Therefore, the present application uses multi-layer coating to rationally design parameters such as the component dosage and particle size structure in each coating layer so that the adjacent coating layers satisfy the above-mentioned specific relationship, thereby improving the conductive network structure of the entire negative electrode plate, so that the negative electrode plate can still provide the battery with good dynamic performance, especially rate performance, cycle stability, etc. on the basis of a larger thickness.
[0052] In some embodiments of the present application, the thickness H of any of the coatings satisfies: 50μm≤H≤150μm. The thickness may be any value of 50μm, 60μm, 80μm, 90μm, 100μm, 150μm, or an interval formed by any two values. As the thickness increases, the secondary battery can be endowed with a higher energy density. Through the reasonable design of the negative electrode plate in the present application, the battery can be endowed with both high energy density and excellent charge and discharge kinetics within this thickness range.
[0053] In some embodiments of the present application, the multilayer negative electrode satisfies: 0.1% ≤ C ≤ 9%. C represents the content of the conductive agent in a certain coating. The conductive agent can give the battery excellent ion conductivity and capacity within the above-mentioned suitable range. The value of C can be: any value of 0.1%, 0.6%, 0.8%, 3%, 6%, 9%, or an interval formed by any two values.
[0054] In some embodiments of the present application, the multilayer negative electrode satisfies: 1% ≤ B ≤ 15%. B represents the content of silicon material in a certain coating. The theoretical specific capacity of silicon material is high, which can reach 400-4000 mAh / g, and can give the battery a high energy density; and it has a low lithium deintercalation potential, which also helps to avoid lithium precipitation on the surface during charging, thereby improving the safety performance of the battery. Therefore, silicon material is one of the promising negative electrode active materials in this field. When the content of silicon material in the coating is within the above range, the battery can have both high specific capacity and kinetic cycle performance. The value of B can be any value of 1%, 4%, 6%, 10%, 12%, 15%, or an interval formed by any two values.
[0055] In some embodiments of the present application, based on the total weight of any of the coatings, the mass percentage of the carbon material is recorded as A, satisfying: 70% ≤ A ≤ 99%. Carbon material is one of the common negative electrode active materials in the field, has excellent electrical conductivity, and can give the battery excellent ion conductivity and rate performance. The carbon material can give the battery excellent ion conductivity and kinetic cycle stability within the above-mentioned appropriate range. The value of A can be any of 71.5%, 81%, 89.8%, 95.3%, 98.3%, or an interval formed by any two values.
[0056] In addition, the particle size structure parameters of the negative electrode active material (including) will also affect its distribution in the coating. Appropriate particle size distribution can ensure faster insertion and extraction of lithium ions. Therefore, reasonable adjustment of the particle size distribution of the active material helps to further improve the compaction density of the electrode and thus improve the volume energy density of the battery, while improving the cycle and rate performance of the battery.
[0057] In some embodiments of the present application, the particle size of the silicon material satisfies: 1 μm≤Dv10≤6 μm. The value of Dv10 can be any value of 1 μm, 2 μm, 3 μm, 5 μm, 6 μm, or an interval formed by any two values.
[0058] In some embodiments of the present application, the particle size of the silicon material satisfies: 8 μm ≤ Dv50 ≤ 10 μm. The value of Dv50 can be any value among 8 μm, 9 μm, 10 μm, or an interval formed by any two values.
[0059] In some embodiments of the present application, the particle size of the silicon material satisfies: 12 μm ≤ Dv90 ≤ 16 μm. The value of Dv90 can be any value of 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, or an interval formed by any two values.
[0060] In some embodiments of the present application, the particle size of the carbon material satisfies: 1μm≤Dv10'≤8μm, Dv10' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 10%, in μm. The value of Dv10' can be any value of 1μm, 3μm, 5μm, 8μm, or an interval formed by any two values.
[0061] In some embodiments of the present application, the particle size of the carbon material satisfies: 9μm≤Dv50'≤14μm, Dv50' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 50%, in μm. The value of Dv50' can be any value among 9μm, 11μm, 13μm, 14μm, or an interval formed by any two values.
[0062] In some embodiments of the present application, the particle size of the carbon material satisfies: 16μm≤Dv90'≤24μm, Dv90' represents the particle size corresponding to 90% of the cumulative volume of the carbon material, in μm. The value of Dv90' can be any value of 16μm, 18μm, 20μm, 22μm, 24μm, or an interval formed by any two values.
[0063] In some embodiments of the present application, based on the total weight of any of the coatings, the mass percentage of the binder is recorded as D, which satisfies: 0.1%≤D≤6%. The value of D can be any value of 0.1%, 0.5%, 1%, 2%, 3%, 6%, or an interval formed by any two values.
[0064] In the present application, the types of carbon materials and silicon materials are not limited. Common carbon negative electrode active materials, silicon negative electrode active materials, and silicon-carbon composite negative electrode active materials in the field can all be used in the present application to prepare multilayer negative electrodes. For example, the carbon material includes but is not limited to at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, and soft carbon. The silicon material includes but is not limited to at least one of silicon dioxide and silicon monoxide. The silicon-carbon composite negative electrode active material includes but is not limited to at least one of carbon-coated silicon oxide, carbon-coated pre-lithiation silicon oxide, and carbon-coated pre-magnesiation silicon oxide.
[0065] In the present application, the types of conductive agents and binders are not limited. Common conductive agents and binders in the art can be used in the present application and can be selected as needed. For example, the conductive agent includes but is not limited to at least one of conductive graphite, carbon black, carbon fiber, carbon nanotubes, and graphene. The binder includes but is not limited to at least one of polyvinyl alcohol, polyacrylic acid, polytetrafluoroethylene, sodium carboxymethyl cellulose, SBR rubber, fluorinated rubber, polyolefin, polyvinylidene fluoride, and polyurethane.
[0066] In the present application, the type of negative electrode current collector is not limited, and any common negative electrode current collector in the art can be used to prepare the negative electrode sheet in the present application. In some embodiments, the negative electrode current collector can preferably be copper foil or carbon-coated copper foil.
[0067] In the present application, the preparation process of the multilayer negative electrode comprises the following steps:
[0068] (1) dissolving the carbon material, silicon material, conductive agent and binder in a solvent and stirring to form a uniform slurry, and preparing n portions of slurry by the same method. The components and compositions of the n portions of slurry may be the same or different according to actual needs;
[0069] (2) The n portions of uniform slurry are discharged simultaneously through a die head having n discharge parts, and are dried in a drying oven and rolled by a roller press to obtain the multilayer negative electrode.
[0070] In the present application, the thickness of the active material layer is determined by the opening width of the die head and the roller pressure.
[0071] In some embodiments, the solvent used to form the slurry in step (1) includes, but is not limited to, at least one of N-methylpyrrolidone and water. It should be noted that in the present application, any of the above-mentioned "total weight of the coating" does not include the solvent used to form the slurry during the calculation process.
[0072] A second aspect of the present application provides a secondary battery, which includes a positive electrode plate, an electrolyte, a separator, and the multilayer negative electrode described in the first aspect of the present invention.
[0073] The positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector, wherein the positive active layer includes a positive active material. The present application does not limit the type of positive active material, and the commonly used positive active materials in the art can be used to prepare a secondary battery in the present application. The positive active material includes but is not limited to at least one of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide (NCM).
[0074] In the present application, the type of positive electrode current collector is not limited. The positive electrode current collector can be made of metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; carbon materials such as carbon cloth and carbon paper; composite materials formed by polymers and metal layers. In some embodiments, the positive electrode current collector is preferably made of aluminum foil.
[0075] In some embodiments, the type of solvent used to form the positive electrode slurry is not limited, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive agent, the binder, and the dispersant.
[0076] In the secondary battery described in the present application, the type of the separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.
[0077] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, placing the separator between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.
[0078] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc. There is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0079] The third aspect of the present application provides an electric device, which includes the secondary battery described in the second aspect of the present application. The electric device can be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle can be a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and a railway electric tool, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.
[0080] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.
[0081] Examples 1 to 9, Comparative Examples 1 to 3
[0082] A multilayer negative electrode is provided, and a preparation method thereof comprises the following steps:
[0083] (1) According to the formula in Table 1, a carbon material (artificial graphite is selected in this embodiment), a silicon material (SiO is selected in this embodiment), a conductive agent acetylene black (Super P) and a binder polyacrylic acid are dissolved in deionized water and stirred to form a uniform slurry, and three portions of slurry are prepared by the same method;
[0084] (2) The three portions of slurry prepared in step (1) were respectively fed into a die head having three openings through three feeding ports, and then discharged simultaneously and coated on a 4.5 μm copper foil, and then dried in a drying oven and rolled on a roller press to obtain a multilayer negative electrode having three active material layers coated on a current collector (with a compaction density of 1.6 g / cm 3 ), wherein the relevant parameters of each layer in the three-layer negative electrode are detailed in Table 1.
[0085] Table 1
[0086]
[0087]
[0088] Note: In Table 1, the particle size of silicon material is represented by Dv90, Dv50, and Dv10; the particle size of silicon material is represented by Dv90', Dv50', and Dv10'.
[0089] The negative electrode sheets prepared in the above examples and comparative examples were prepared into secondary batteries, and then the dynamic performance of the secondary batteries was tested.
[0090] The preparation of the secondary battery includes the following steps:
[0091] Positive electrode preparation
[0092] The positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 The mixture of acetylene black (O2), conductive agent and polyvinylidene fluoride (PVDF) in a mass ratio of "positive electrode active material: acetylene black: PVDF" = 94:3:3 was uniformly mixed and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed black slurry was coated on both sides of the aluminum foil, baked, rolled and cut into pieces to obtain a compacted density of 0.33 g / cm 3 The positive electrode.
[0093] Electrolyte preparation
[0094] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC) are mixed in a volume ratio of 3:6.5:0.5 to obtain a mixed organic solvent, and then LiPF6 is dissolved in the mixed organic solvent, and after mixing evenly, an electrolyte with a lithium ion concentration of 1 mol / L is obtained;
[0095] Secondary battery assembly
[0096] The prepared positive electrode sheet, separator (polypropylene separator, Celgard 2300, purchased from Celgard, USA), and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then wound into a battery cell. After hot pressing and shaping, the tabs are welded to obtain a bare cell, which is then loaded into a square aluminum shell. After top and side sealing, liquid injection (electrolyte), formation, sorting and other processes, a lithium-ion secondary battery is obtained.
[0097] The performance test of secondary batteries is as follows:
[0098] (1) Normal temperature internal resistance (DCR) test: At 25±2°C, the square aluminum shell lithium ion secondary batteries obtained in the examples and comparative examples were charged to 4.25V at 1C, then discharged at 1C for 30 min, adjusted to 50% SOC, and then discharged at 3C constant current pulse for 10s and then charged for 10s. DCR was calculated as (voltage before pulse discharge - voltage after pulse discharge) / discharge current × 100%. The recorded results are shown in Table 2.
[0099] (2) Room-temperature rate charging test: At 25±2°C, the square aluminum-shell lithium-ion secondary batteries obtained in the examples and comparative examples were discharged at 1C to 2.5V, and then charged to 4.25V at yC. The above discharge and charge process was repeated with y=0.33, 0.5, 1, 2, and 3, respectively. The capacity obtained by charging at 0.33C was taken as the initial discharge capacity. The capacity retention rates at 1C, 2C, 3C, and 4C were calculated as the capacity obtained at yC / initial discharge capacity×100%. The recorded results are shown in Table 2.
[0100] (3) Normal temperature cycle performance test: At 25±2°C, the square aluminum shell lithium ion secondary batteries obtained in the embodiment and the comparative example were subjected to charge and discharge cycle tests at a charge and discharge rate of 2.2C / 1C in the range of 2.5 to 4.25V, and the number of cycles at which the battery capacity retention rate was 80% was recorded. 80% capacity retention rate = discharge capacity / first cycle discharge capacity × 100%, and the recorded data are shown in Table 2.
[0101] Table 2
[0102]
[0103]
[0104] From the above results we can see that:
[0105] The lithium-ion battery prepared in the embodiments of the present application exhibits better comprehensive performance, that is, when the thickness of the electrode plate is ≥200μm: DCR≤0.42mΩ; 3C charging capacity retention rate ≥84.8%; 80% capacity retention cycle number at 25°C>1050 weeks; therefore, the multilayer electrode prepared by meeting the above conditions of the present application can effectively reduce the DCR of the lithium battery, thereby improving the fast charging performance of the lithium battery and increasing its service life, so as to meet the market's increasing demand for actual products.
[0106] In Table 1 and Table 2, it can be seen from the comparison between Example 1 and Comparative Example 1 that when the total thickness of the electrodes is the same, the application of the multi-layer electrode solution can effectively reduce the DCR of the lithium battery, thereby improving the fast charging performance of the lithium battery and optimizing the cycle life of the lithium battery. This is because the application of the multi-layer electrode solution can more reasonably distribute the arrangement of the additive components in the electrode, further improving the conductivity of the electrode.
[0107] In Table 1 and Table 2, by comparing Examples 2 and 5 with Comparative Examples 2-4, it can be seen that when the functional relationship between the content of each component in the multilayer electrode, the particle size distribution and the electrode thickness is formed, m Satisfy 0.2≤f m When ≤1.2, the conductive agent and electrode structure corresponding to the change in silicon content can effectively improve the poor electronic conductivity of silicon materials. Combined with the advantage of strong ionic conductivity of silicon materials, the DCR of lithium batteries can be significantly reduced, and the fast charging performance and cycle life can also be significantly improved.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A multilayer negative electrode, characterized in that: The multilayer negative electrode comprises a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises different coatings stacked in layers, wherein the coatings in the negative electrode active layer are sequentially recorded as the first layer, the second layer, ... to the mth layer from the side close to the current collector, wherein the number of layers of the coatings is m≥3, and any of the coatings independently comprises: a carbon material, a silicon material, a conductive agent, and a binder, and the multilayer negative electrode satisfies the following relationship: 0.2≤f m =|K m / K m-1 -K m-1 / K m-2 | / S m-1 ≤1.2 K=C×H / B S=(Dv90-Dv10) / Dv50 K m ≠K m-1 ≠K m-2 In the formula, C represents the mass percentage of the conductive agent based on the total weight of any of the coatings; B represents the mass percentage of the silicon material based on the total weight of any of the coatings; H μm represents the thickness of any of the coatings; Dv10μm represents the particle size corresponding to when the volume of the silicon material reaches 10% cumulatively; Dv50μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 50%; Dv90μm represents the particle size corresponding to when the cumulative volume of the silicon material reaches 90%; The subscript m refers to the mth layer of coating; the subscript m-1 refers to the m-1th layer of coating; The subscript m-2 indicates the m-2th layer of coating.
2. The multilayer negative electrode according to claim 1, characterized in that: Satisfies: 50μm≤H≤150μm.
3. The multilayer negative electrode according to claim 1, characterized in that: Satisfies: 0.1%≤C≤9%.
4. The multilayer negative electrode according to claim 1, characterized in that: Satisfies: 1%≤B≤15%.
5. The multilayer negative electrode according to claim 1, characterized in that: Based on the total weight of the coating, the mass percentage of the carbon material is recorded as A, and satisfies: 70%≤A≤99%.
6. The multilayer negative electrode according to claim 1, characterized in that: Based on the total weight of the coating, the mass percentage of the binder is recorded as D, which satisfies: 0.1%≤D≤6%.
7. The multi-layer negative electrode according to claim 1, characterized in that: The particle size of the silicon material satisfies at least one of the following characteristics: (1) 1μm≤Dv10≤6μm; (2) 8μm≤Dv50≤10μm; (3)12μm≤Dv90≤16μm.
8. The multi-layer negative electrode according to claim 1, characterized in that: The particle size of the carbon material satisfies at least one of the following characteristics: (1) 1 μm ≤ Dv10' ≤ 8 μm, where Dv10' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 10%, in μm; (2) 9 μm ≤ Dv50' ≤ 14 μm, where Dv50' represents the particle size corresponding to when the cumulative volume of the carbon material reaches 50%, in μm; (3) 16 μm ≤ Dv90′ ≤ 24 μm, where Dv90′ represents the particle size corresponding to 90% of the cumulative volume of the carbon material, and the unit is μm.
9. A secondary battery, characterized in that: It comprises a positive electrode sheet, a separator, a multilayer negative electrode as claimed in any one of claims 1 to 8, and an electrolyte.
10. An electrical device, characterized in that: The electric device comprises the secondary battery according to claim 9.
Citation Information
Patent Citations
Secondary battery, preparation method therefor and device comprising the secondary battery
CN113875046A
Secondary battery, method for manufacturing the same, and related battery module, battery pack
CN114788044A
Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and device
CN115917780A
Silicon negative electrode sheet, manufacturing method thereof and lithium ion battery
US20210091378A1